Rankine-type cylinders having zero wave resistance in infinitely deep flows. (15th April 2020) - Dambrine, Julien; Noviani, Evi; Pierre, Morgan
Abstract: We prove the existence of a family of immersed obstacles that have zero wave resistance in the context of the 2D Neumann–Kelvin problem. We first build a waveless potential by superposing a source and a sink in a uniform flow for an appropriate choice of parameters. The obstacle is obtained by a combination of streamlines of the waveless potential. Numerical simulations show that the construction is valid for a large set of parameters.